2022
DOI: 10.1093/ntr/ntac064
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Effects of Inhaled Nicotine on the Gut Microbiome

Abstract: Introduction The impact of nicotine, the addictive component of both traditional cigarettes and e-cigarettes, on many physiological processes remains poorly understood. To date, there have been few investigations into the impact of nicotine on the gut microbiome, and these studies utilized oral administration rather than inhalation. This study aimed to establish if inhaled nicotine alters the gut microbiome and the effect of sex as a biological variable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…A mouse study revealed a potentially time-dependent effect of smoking exposure on the increase in Turicibacter[g] abundance [57]. Nevertheless, two other mice studies have reported con icting ndings on this matter [58,59]. In any case, our study contributes new evidence to this ongoing debate from a population perspective.…”
Section: Discussionmentioning
confidence: 58%
“…A mouse study revealed a potentially time-dependent effect of smoking exposure on the increase in Turicibacter[g] abundance [57]. Nevertheless, two other mice studies have reported con icting ndings on this matter [58,59]. In any case, our study contributes new evidence to this ongoing debate from a population perspective.…”
Section: Discussionmentioning
confidence: 58%
“…Finally, interaction of Fe, Mn, butyrate, and nicotine with gut microbiota have been recently highlighted ( Tinkov et al 2021 ; Whitehead et al 2022 ; Nicese et al 2023 ; Xiao et al 2023 ). Hence, potential exploits of the gut-brain axis in amelioration of heavy metal toxicities and/or prevention or delay of neurodegenerative diseases is worth consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, sexdependent effects were found, whereby female adolescent rats displayed lower anxiolytic effects and were more sensitive to the rewarding effect of nicotine than their male counterparts [93,139,140], although others did not find sex differences [107]. Interestingly, the gut microbiome was found to mediate sex-dependent effects related to nicotine metabolism in chronic e-cigarette exposure, and nicotine exposure was found to decrease alpha diversity in females and beta diversity in both sexes [92]. A history of vaping was also associated with stroke, with higher odds for females [109].…”
Section: Central Nervous Systemmentioning
confidence: 99%